Analisis Pengelolaan Keuangan Desa Gita Raja Berdasarkan Permendagri No 20 Tahun 2018 Di Desa Gita Raja Kecamatan Oba Kota Tidore Kepulauan - Hehakaya, Fadhillah Faya Azzala; Hasan, Muhammad Hi; Yunus, Imran (Peneliti.net, 2025)
This study aims to determine how village financial management is carried out in Gita Raja Village, Oba District, Tidore Islands City, based on Permendagri No. 20 of 2018. The main focus of this research is to analyze the application of the principles of transparency, accountability, participation, and orderly and disciplined budgeting in village financial management. Data analysis techniques use qualitative descriptive techniques by reducing data, presenting data, and drawing conclusions (verification), with data collection methods involving interviews with the Village Head, Village Secretary, and Finance Officer, as well as observation and documentation. The results of the study indicate that financial management in Gita Raja Village is generally in accordance with Permendagri No. 20 of 2018. Transparency is evident in the village government's active dissemination of information about the Village Budget (APBDesa) to the community through various media. Accountability is maintained through timely submission of accountability reports to the relevant authorities. Community participation is fostered through the Village Development Planning Meeting (Musrenbangdes), which involves residents in determining development priorities. Budget Discipline and Orderliness Gita Raja Village follows the established budget book and adheres to applicable procedures in budget management, although there are some challenges in financial management, such as a shortage of financial experts.